KEMISKINAN DI BALI - WAYAN YOGI SWARA; I MADE JEMBER (PIRAMIDA, 2011)
Millennium development goals (MDGs) has become an importantreference for the development in Indonesia. In reducing poverty requires asustainable and equitable economic growth sustainable. The size of the successfulachievement of national development, one of them can be seen from the HumanDevelopment Index (HDI). HDI can be described by three indicators of the LifeExpectancy Index, Knowledge Index and Income Index. Through research on thevalue Gross Dosmestic Product (GDP), life expectancy, and the HumanDevelopment Index will be a portrait of the poverty level in a region/country. Thisstudy was conducted to see the extent of poverty in the province of Bali seen fromthe review of the value GDP, life expectancy, and the Human Development Indexduring the period 2005 to 2009.Through this research can be seen how far the realization of millenniumdevelopment goals (MDGs) can be accomplished. This study uses secondary data,using descriptive analysis techniques. From the results of the analysis is knownthat the Human Development Index of Bali Province of 69.10 in 2004, whereas in2009, a 71.52 this puts the Province of Bali is ranked sixteenth for IPM inIndonesia. Judging from the life expectancy indicate that the province of Bali wasin fourth position in Indonesia. Overall economic performance of Bali Province inthe year 2009 has been changed into positive from per capita GDP. In 2009 thenumber of poor people in Bali both rural and urban areas only 181.7 thousandinhabitants or 5.13 percent. The number of poor families in the province of Bali,in 2009 as many as 134,804 families are scattered in nine districts/cities.Suggestion put forward is the development policy should be adapted to localconditions, and design development between top down-bottom up should beconducted in stages. In addition, implementation of development programs shouldfocus on programs involving many people's lives especially those that canalleviate poverty.